Impact of benefit sanctions on unemployment outflow: Evidence from German survey data - Katja Hillmann; Ingrid Hohenleitner (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2012)
Similar to many other European countries, Germany's unemployment policy made a paradigm shift towards activation policy with a tightened monitoring and sanction regime. In our analysis, we examine the impact of benefit sanctions on the probability of getting employed or leaving the labor force. Using a mixed proportional hazard model, we draw causal inference of sanction enforcement on unemployment exit hazards. Based on a survey sample, covering the first three years after implementation of the Hartz IV law in 2005, we find evidence for a positive impact of sanctions on getting employed, but also on leaving the labor market.
Keywords: J48; J63; J64; J68; I38; 330; unemployment benefit sanctions; unemployment duration; employment; nonemployment; mixed proportional hazard estimation